1994
DOI: 10.1017/s0017089500030603
|View full text |Cite
|
Sign up to set email alerts
|

Almost factorisable inverse semigroups

Abstract: 0. Introduction. In [3], McAlister introduced a class of semigroups, called covering semigroups, which were shown to play an important role in the theory of E-unitary covers of semigroups. Strangely, this class of semigroups appears to have received little attention subsequently. It is the aim of this paper to rehabilitate them and to study their properties in more detail. As a first step, we have chosen to rename them almost factorisable semigroups, since they can be regarded as the semigroup analogues of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Example 2. In [18], we showed that an E-unitary inverse semigroup is over a semilattice (in the sense of McAlister [25]) if, and only if, it has an enlargement which is a semidirect product of a group and a semilattice. On the basis of this result, we proved in [18] that every inverse semigroup has an enlargement which is close to being factorisable (what we call almost factorisable), sharpening the results of [24] and [29].…”
Section: Introductionmentioning
confidence: 99%
“…Example 2. In [18], we showed that an E-unitary inverse semigroup is over a semilattice (in the sense of McAlister [25]) if, and only if, it has an enlargement which is a semidirect product of a group and a semilattice. On the basis of this result, we proved in [18] that every inverse semigroup has an enlargement which is close to being factorisable (what we call almost factorisable), sharpening the results of [24] and [29].…”
Section: Introductionmentioning
confidence: 99%
“…Now we establish that, for inverse semigroups, almost factorizability in our sense coincides with the usual notion of almost factorizability (see [11,12]). Conversely, assume that S is an inverse semigroup and U is a completely simple subsemigroup in O(S) within properties (AF1) and (AF2).…”
Section: Lemma 8 For Any H Hmentioning
confidence: 56%
“…The notion of an almost factorizable inverse semigroup was introduced by Lawson [11] (see also [12]) as the semigroup analog of a factorizable inverse monoid. Among others, he established (see also [13] where the main ideas and some of the results were implicit) that the almost factorizable inverse semigroups are just the homomorphic images (or, equivalently, the idempotent separating homomorphic images) of semidirect products of semilattices by groups.…”
Section: Introductionmentioning
confidence: 99%
“…11.1; [32], section 8.1) and latterly the re ‡ection monoids of Everitt and Fountain [8]. Appropriate generalisations of the concept were developed: signi…cantly, Lawson [17] identi…ed the appropriate generalisation from monoids to semigroups as almost factorizable semigroups, which had been used in McAlister [25]; for an account, see section 7.1 of [18]. Tirasupa [35] examined the Cli¤ord by semilattice case and Mills [29] the group by aperiodic case.…”
Section: Some Historymentioning
confidence: 99%